Effects of oral L-carnitine and DL-carnitine supplementation on alloxan-diabetic rats - Bazotte,Roberto Barbosa (2012)
The effect of oral L-carnitine (LC) or DL-carnitine (DLC) supplementation during one or four weeks (200 or 400 mg.kg-1.day-1) in diabetic rats was investigated. After the supplementation period, the blood was collected for the evaluation of total (TC) and free L-carnitine (FC), glucose, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triacylglycerol. Tissues were collected for the determination of TC and FC concentrations. The carnitine supplementation did not change levels of glucose, total cholesterol, HDL-C and LDL-C in the blood. Diabetic rats showed hypertriacylglycerolemia and decreased blood and tissue levels of FC and TC. Normalization of the blood triacylglycerol and increased blood and tissue levels of FC and TC were observed with the LC or DLC supplementation. However, the hyperglycemia remained unchanged. Thus, the reduction of blood triacylglycerol obtained with carnitine supplementation in the diabetic rats did not depend on an amelioration in the glycemia and was mediated partly at least by an increment of serum and tissue concentrations of FC and TC.